The relationship between quality of life and anthropometric measurements in premenopausal and postmenopausal among turkish women - Köse, Beril; Yeşil, Esen; Türker, Perim Fatma; Akçil Ok, Mehtap; Bayram, Sinem; Köseler Beyaz, Esra; Özdemir, Merve; Müftüoğlu, Selen; Tayfur, Muhittin; Aksoydan, Emine; Ercan, Aydan; Saka, Mendane; et al. (Progress in Nutrition, 2019)
The aim of this work was to investigate whether there is a relationship between anthropometric measurements and quality of life scores during pre and postmenopouse period. A descriptive study was carried out on 1276 women (40–64 years). Demographic features, socioeconomic attributes and anthropometric measurements were considered using a validated instrument the Turkish version of the EUROHIS (WHOQOL-8.Tr) was performed. Significant body mass index (BMI), height, waist circumference, hip circumference, waist/ height ratio differences were determined by comparing pre and postmenopausal women (p<0.05). Significantly lower quality of life scores were observed in premenopausal women (p<0.05). BMI was determined as significant predictor for quality of life for each group. The number of pregnancy, number of live birth, number of stillbirth and waist/height ratio did not show significant association with quality of life. The age of first pregnancy was stated as significant predictor for quality of life just for premenopausal women. In our study, quality of life increased as the BMI decreased in pre and postmenopausal women. Significantly lower WHO-8 EUROHIS scores were observed in premenopausal women. The age of first pregnancy affected the life quality in positive way in just premenopausal women. As the age of first pregnancy increased, quality of life score increased in premenopausal women.